YOUTH CAMPS: PREFERENCE OF ACTIVITIES BY GENDER AND AGE (Fiep Bulletin - online, 2013)
The entertainment has been gaining increasing importance in modern society, especially as a means of social development, taking the holiday as a colony of them. This work was to sample a Vacation colony held at the Federal University of Juiz de Fora (UFJF) in the year 2008, aimed at young people in poor communities around the UFJF. Purpose: Among the activities addressed in the colony of holidays which were better preference for gender, and age. Methodology: questionnaire evaluation of the colony, where they were interviewed 30% of children who ranged from ages 4 to 16 years, where he assessed the activity in which children liked most and least liked it. Results: 59% of the boys chose football, 14% preferred bed elastic and less like that was burned (12%) cited the girls 35% and 31% prefer burning bed elastic and activity that was the least liked football (16%). Conclusion: It must fit the activity in relation to gender and age group, as well as make further similar studies.
Keywords: Youth camps; Favorite activities and Social development